Bibliometric Analysis of BiFeO3 Nanoparticle Research Development Using VOSviewer Application - Al-Ghani, Ranggaweny (Jurnal Nusantara Mengabdi, 2025)
Purpose: This research aimed to conduct analysis in the research of BiFeO3 nanoparticles through bibliometric analysis techniques with computational mapping used VOSviewer application. Methodology/approach: By using the publish or perish reference management tool and the Google Scholar database's collection of research article data to obtain research data article. The search was focused on the article's title and abstract with "BiFeO3 nanoparticles" was used as the search term, and literature review method was used according to related topics. This study's research era covers the most recent 10 years (2012 to 2022) from publications in both national and international journals that Google Scholar has indexed. Results/findings: From the search result, there were 996 journal articles related to keywords. The range of journal articles searched from the Google Scholar database is the last decade (from 2012 to 2022). Conclusions: Bibliometric analysis using VOSviewer shows that research on BiFeO3 nanoparticles (2012–2022) formed 8 clusters with 996 articles. After rising until 2018, publication trends declined, indicating significant opportunities for further development and broader research connections. Limitations: This limitations of this research was focused on the development trend of BiFeO3 nanoparticle research in the last decade shows a slight fluctuation but still an uptrend from time to time. Contribution: This research is expected to provide information on research development trends during the last decade for researchers who want to conduct research, especially related to the topic of BiFeO3 nanoparticle.